Interaction of Pb, Ni and Cd with aquatic humic substances of amazonian blackwater rivers - Constantino, Isabela C. [UNESP]; Viana, Juliana G. [UNESP]; Teixeira, Priscila A. [UNESP]; Moreira, Altair B. [UNESP]; Gama, Giovanna P.; Paschoal, Fabiana M.M.; Sargentini, Ézio; Bisinoti, Márcia C. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
In this study, the extraction and characterization of aquatic humic substances (AHS) from two blackwater rivers in the Amazon basin was carried out in order to assess the seasonal effects in the AHS structure. In addition, an investigation of the complexing capacities (CC) of the structures containing the metal ions CdII, NiII and PbII was also done. The characterization (of the AHS) was done using UV-Vis, molecular fluorescence, and infrared spectroscopy. AHS from the Negro River showed more aromatic characteristics in its structures and molecular weight, than the AHS from the Carú River. The AHS studied presented a seasonal pattern characterized by higher humification levels during the rainy season. For all the metals, the AHS complexing capacity was higher for the Negro River. The highest complexing capacities were observed for the NiII assays, which were 0.56 and 0.12 μmol NiII mg-1 dissolved organic carbon (DOC), for AHS RN and AHS RC-II, respectively. We concluded that the transport, bioavailability, and toxicity, of these metal species should be higher for Carú River.
Keywords: Amazon; Blackwater; Characterization; Complexation; Humic substances; Negro River